Vimentin may reflect areas of pathologic involvement in biopsies from patients with autoimmune skin diseases - Ana Maria Abreu Velez; Daniel Alberto Vásquez Hincapié; Michael S. Howard (Our Dermatology Online, 2014)
Introduction: Autoimmune bullous skin diseases (ABDs) represent a group of disorders of the skin and mucosa commonly associated with deposits of immunoglobulins, complement and fibrinogen, and usually directed against distinct adhesion molecules. After studing these diseases for many years, we noted alterations not only between the cells junctions of the epidermis and/or the dermal/epidermal junction, but also in dermal skin appendageal structures and in mesenchymal tissue around the blisters. Based on our findings, we wanted to determine if the observed patterns of autoimmunity correlated with cutaneous vimentin expression. Materials and Methods: Archival biopsies previously diagnosed with ABDs by clinical, hematoxylin and eosin (H&E) and direct and/or immunofluorescence data were stained with antibodies directed against vimentin via immunohistochemistry (IHC). We tested 30 patients affected by endemic pemphigus, 30 controls from the endemic area, and 15 normal controls. We also tested 30 biopsies from patients with bullous pemphigoid (BP), 20 with pemphigus vulgaris (PV), 8 with pemphigus foliaceus, 14 with dermatitis herpetiformis (DH) and 3 with Senear-Usher syndrome. Results: The H&E, DIF and vimentin patterns of positivity in the different ABDs confirmed that vimentin was compartmentalized around areas of dermal inflammation, around skin appendages and in epidermal, dermal and mesenchymal cell junction areas. Conclusion: Vimentin may be a useful tool for highlighting patterns of microenvironmental tissue alteration in multiple ABDs. The vimentin staining pattern observed was analogous to that we have previously described for proteases and protease inhibitors in patients affected by ABDs, expanding the concept that the autoimmune process extends beyond cell junctions.